The selective heating of pyrite in coal using microwave energy - Wardle, Peter (2011)
The objective of this research project was to investigate the effect of microwave treatment on the conversion of pyrite in coal in order to enhance its magnetic properties and to aid subsequent desulphurisation by magnetic separation. Key areas of this investigation include:- a review of the fundamental theoretical aspects of heating in an applied microwave field, a detailed literature survey of the potential applications of microwave heating to aid coal desulphurisation, a study of the transformation mechanisms of pyrite by microwave and conventional heating methods, a comprehensive review of the influence of heterogeneity on the dielectric properties of coals and the effect of high power microwave heating on the decomposition of pyrite in a high sulphur coal.